Phenotypic traits and resource quality as factors affecting male reproductive success in a toadfish. (30th January 2018) - Bose, Aneesh P H; Cogliati, Karen M; Luymes, Nick; Bass, Andrew H; Marchaterre, Margaret A; Sisneros, Joseph A; Bolker, Benjamin M; Balshine, Sigal
Abstract : In nature, it can be challenging to figure out whether success at attracting mates and reproducing is due to something intrinsic about an individual or something about the quality of the resources they possess. In a series of lab and field studies using the plainfin midshipman fish, we show that both factors are complex and that resource quality can impose a limit on reproductive success regardless of the quality of the resource owner. Abstract: A male's reproductive success often depends on both his phenotypic quality and the quality of the resources he controls. An important and longstanding challenge for evolutionary biologists has been to disentangle these 2 often-correlated factors. Here, we present a large multiyear, multipopulation field study along with complementary laboratory experiments aimed at disentangling the effects of male quality and nest quality in driving male reproductive success in the plainfin midshipman fish, Porichthys notatus . We investigate how these factors are linked to reproductive success using a number of different reproductive success components, including female attraction, cuckolder male attraction, egg acquisition, and rearing success. We show in the field that both male size and nest size are important correlates of reproductive success in this paternal care-giving species, but also that nest size can impose a limit on reproductive success regardless of the quality of the male nest owner. Females in the laboratory prefer large males when nest size is held constant, but females show no detectable preference for larger nests when nest size is varied and male size is held constant. We also explore a suite of additional male and nest traits—including male body condition, sonic organ investment, nest species richness, and nest density. Our results highlight how male and resource quality are multivariate concepts that incorporate information from the male phenotype, the ecological environment, and even the social environment and shape mating systems by influencing an animal's choice of mating partners and nesting sites.